Principles and practices of assessment : a guide for assessors in the FE and skills sector - Gravells, Ann (Los Angeles ; London : SAGE ; Learning Matters, 2016)
This new third edition, updated in line with recent changes and qualification in the further education and skills sector provides you with all the information you need to complete the assessment units for the Award and Certificate in Education and Training or the assessment part of the TAQA qualification.
Previously published by Learning Matters as Principles and practice of assessment in the lifelong learning sector.
Includes bibliographical references and index.
IQAC
Karim International
Keywords: Continuing education; Educational tests and measurements